Determinant Factors of Baby Blues Syndrome among PostpartumMothers: A Literature Review - Izzati, Najla Malihah; Calista, Aatifah Dihyan; W.A, Sudarningayuti Lintang; Salvira, Indira Khaznati; Herbawani, Chahya Kharin (Tadulako University, 2025)
Baby blues is a common psychological condition experienced by postpartum mothers, with a prevalence of 33% shows that there is still a lack of attention to maternal mental health as an important part of the recovery process and early parenting. This study aims to identify the factors that cause baby blues in postpartum mothers. This study used the literature review method, searching for scientific articles through the Google Scholar, Garuda, and PubMed databases. Using inclusion criteria that focused on qualitative and quantitative research on baby blues published in the last 5 years and the PRISMA approach. Articles selected were relevant to the topic and aligned with the research objectives. The results of the review showed that baby blues syndrome is influenced by various determinant factors which are divided into two main categories, namely internal and external factors. Internal factors include hormonal changes that cause emotional instability and types of childbirth, such as Sectio Caesarea, which can potentially trigger post-traumatic stress. External factors include lack of emotional and social support from husband, family, and health workers; the mother's demographic and socioeconomic conditions; and the role of health workers in providing responsive and supportive delivery services. In conclusion, various factors such as hormonal instability, traumatic childbirth, limited social support, and the less than optimal role of health workers have been shown to contribute to the occurrence of baby blues syndrome.